Colloid cyst of third ventricle: Histopathological and ultrastructural study - Karki, Prasanna; Aryal, Sameer Chhetri; Aryal, Gopi; Panth, Rajesh; Bohara, Manoj; Joshi, Sumit; Paudel, Prakash; Shah, Damber Bikram; Sharma, Gopal Raman (Journal of Pathology of Nepal, 2019)
Cysts occupying the third ventricle are rare lesions and may appear as an unusual cause of hydrocephalic crisis. A 40-year old woman with headache and one episode of fainting attack was diagnosed with a cystic lesion in the third ventricle after brain MRI study. She was operated with the pre-operative diagnosis of a colloid cyst. A yellowish, thick and mucoid cyst was observed intra-operatively. The total removal of the cyst was done along with the cyst wall. On histopathological evaluation, the cyst wall was lined by ciliated cuboidal to pseudostratified columnar epithelium resting on an eosinophilic basement membrane. The ultrastructural study showed the characteristic 9+2 pattern of cilia. Immunohistochemistry showed positive staining for epithelial membrane antigen (EMA), cytokeratin (CK), and negative staining for Glial fibrillary acidic protein (GFAP). Histopathological and ultrastructural findings confirm the diagnosis of a colloid cyst of third ventricles favoring the endodermal origin of the cyst.